Vetiver grass - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Vetiver grass: technical information package volumes 1 and 2 1993 The World Bank Vetiver Information Network, 1818 H Street NW Washington DC 20433, USA